Effect of Postural Stability Exercises on Gait Parameters in Children with Spastic Diplegia Cerebral Palsy: An Experimental Trial - Latika Gulyani; Kanniapan Vadivelan; Anshika Singh; Shagun Agarwal; Sumit Raghav (Фізична реабілітація та рекреаційно-оздоровчі технології, 2024)
Postural stability helps maintain the position of the body within the support area to maintain control, but this postural stability is affected in children with cerebral palsy during static or dynamic activities. However, the practical application of postural stability exercises combined with muscle strengthening has not been studied in spastic diplegia cerebral palsy children with gait difficulties.